Pengembangan Video Motion Graphic Larutan Elektrolit dan Non Elektrolit untuk Meningkatkan Minat Belajar Siswa SMA - Anisa Rahmawati; Agus Kamaludin (Postgraduate, University of Mataram, 2023)
Electrolyte and non-electrolyte solution material is an abstract chemical material. Therefore, learning media is needed so that the material becomes concrete to increase students' interest in learning and understanding and avoid misconceptions. This research aims to develop a motion graphic video on the material of electrolyte solution and non-electrolyte solution and determine the quality of the resulting product. This research is development research (R&D) with a 4D model (Define, Design, Development, and Disseminate), but this research is only up to the development stage. One material expert, one media expert, and four reviewers (senior high school chemistry teachers) assessed the product. Material experts' results of the product quality assessment get 95% in the Very Good category, media experts get 90% in the Very Good category, and reviewers get 91.25% in the Very Good category. In addition, the results of student responses obtained 98%. Based on the assessment results, it can be concluded that motion graphic video can be used as an alternative learning media on electrolyte and non-electrolyte solutions to increase student interest in learning.